Isolating and modifying cellulose from waste papers as flocculant for treating drinking water. (1st March 2022) - Yusoff, Nor Aida; Mohtar, Safia Syazana; Tengku Malim Busu, Tengku Nur Zulaikha; Md Noor, Ahmad Mujahid; Shaari, Norsalliana; Mat, Hanapi
Abstract: In this study, cellulose was extracted from waste paper using alkaline and bleaching treatments. The flocculation performance of six quaternized cellulose (QC) samples (QC-1, QC-5, QC-10, QC-15, QC-20, and QC-30) was evaluated through kaolin suspension using the standard jar test method at varying flocculant dosages, kaolin concentrations, pH values, and settling times. The cellulose content of the waste paper and extracted celluloses were 68.6% and 78.1%, respectively. Fourier-transform infrared spectroscopy, x-ray diffraction, thermogravimetric analysis, and scanning electron microscopy showed that the waste paper properties changed after chemical treatment, confirming that the extracted product was cellulose. The QC derivatives were homogeneously synthesized by reacting the extracted cellulose with 3-chloro-2-hydroxypropyl trimethylammonium chloride (CHPTAC) in the aqueous medium of sodium hydroxide/urea. QC-15 exhibited a highly effective flocculation capability (99.67%) compared to alum (83.91%), with good performance in a wide pH range. The flocculation kinetics (kNo: 5.9 × 10 −1 s-1 ) supported this finding. QC-15 removed 99.67% of turbidity compared to alum (83.9%). Besides, filtration of the conditioned sludge with QC-15 was relatively easy, with low specific resistance compared to the commercial alum. Overall, Q-15 was an effective and environmentally friendly flocculant with potential application for treating drinking water.